A rare differential diagnosis of excessive daytime sleepiness - Artery of Percheron territory infarct - Giuliano da Paz Oliveira; Giselle Truzzi; Fernando Cascio Barros Lima; Fernando Morgadinho Santos Coelho (Sleep Science)
Stroke is an example of neurological diseases that can commonly drives Excessive Daytime Sleepiness (EDS). Extensive strokes with brain edema can leave a brain herniation and coma. Other causes of EDS after stroke are strategic lesions at Thalamus and brainstein. A 56-year-old man, right handed, with hypertension and hypercholesterolemia was admitted at Emergency Room due to 5 days onset of EDS, memory impairment, and left-sided weakness. A brain magnetic resonance imaging showed paramedian thalamic hyperintensity with rostral midbrain hyperintensity extending along the pial surface of the interpeduncular fossa. The artery of Percheron (AP) is an unusual anatomical variation that originates from the posterior cerebral artery and irrigates the paramedian regions of the thalamus and part of the midbrain. It is important the clinical suspicions with detailed drowsy patients history. Awareness of the clinical and neuroimaging features of this stroke syndrome is essential for timely diagnosis and appropriate management.